2021
DOI: 10.3390/vaccines9111362
|View full text |Cite
|
Sign up to set email alerts
|

A Community-Based Management of COVID-19 in a Mobile Container Unit

Abstract: Vaccine uptake is a multifactor measure of successful immunization outcomes that includes access to healthcare and vaccine hesitancy for both healthcare workers and communities. The present coronavirus disease (COVID-19) pandemic has highlighted the need for novel strategies to expand vaccine coverage in underserved regions. Mobile clinics hold the promise of ameliorating such inequities, although there is a paucity of studies that validate environmental infection in such facilities. Here, we describe communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Compared to two other mobile medical facilities designed and published on 2021, the Smart Pod mobile clinic [ 33 ] and the mobile eye hospital [ 34 ], the advantages and disadvantages of the mobile medical station of this study are presented and discussed. A Smart Pod is a mobile container unit built to participate in the community-based management of COVID-19 in the US in response to the burgeoning need for testing and vaccine delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to two other mobile medical facilities designed and published on 2021, the Smart Pod mobile clinic [ 33 ] and the mobile eye hospital [ 34 ], the advantages and disadvantages of the mobile medical station of this study are presented and discussed. A Smart Pod is a mobile container unit built to participate in the community-based management of COVID-19 in the US in response to the burgeoning need for testing and vaccine delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Teledermatology requests were consulted in an average time of 5 h and 14 min, and prevented 46 evacuations [ 164 ]. Use of mobile clinics as facilities for procedures may be a solution for managing dermatoses in soldiers, and were effective during the COVID-19 pandemic [ 165 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…Mobile clinics may be a consideration to offer another way to perform biopsies. For instance, Petrova et al 4 recently demonstrated the utility of the SmartPod mobile clinic in delivering COVID-19 vaccinations in an underserved area in Houston, Texas. Moreover, suboptimal image quality (in store-and-forward TD) impedes the rendition of accurate diagnoses.…”
mentioning
confidence: 99%